Overview of Risk Factors Associated with Drug-Resistant Tuberculosis at RSU. Imelda Pekerja Indonesia Medan, 2025 - Syahrul Handoko Nainggolan; Basri Basri; Andrey Surya Putra (Benih : Journal of Midwifery, 2026)
Multidrug-Resistant Tuberculosis (MDR-TB) is a form of tuberculosis resistance to at least two first-line anti-tuberculosis drugs, namely Isoniazid (INH) and Rifampicin (RMP), with or without resistance to other anti-tuberculosis drugs. MDR-TB can be influenced by various factors, including age, gender, education level, income, occupation, medication adherence, knowledge, attitude, stigma, smoking habits, the role of Treatment Supervisors (PMO), and drug side effects. This study aimed to identify risk factors associated with drug-resistant tuberculosis at RSU IPI Medan. This study employed a descriptive research design with a purposive sampling technique. The total number of respondents was 27 patients. The results showed that most respondents were aged 36–45 years (29.6%), male (59.3%), had a senior high school education (40.7%), worked as self-employed individuals (33.3%), and had low income levels (62.96%). Respondents who smoked accounted for 59.3%. All respondents had good PMO support (100%). Most respondents experienced drug side effects (92.6%), were adherent to medication (74.7%), had good knowledge (74.7%), and demonstrated positive attitudes (81.48%). Community stigma toward patients was categorized as low (59.26%), while patient self-stigma was considered high (55.56%). It is expected that the findings of this study can serve as a source of information and educational material to support the prevention of drug-resistant tuberculosis.